(untitled) (KULT_online, 2009)
Edited by Günther Bittner, the proceedings Ich bin mein Erinnern (I Am My Remembering) explicitly address the nature of autobiographical memory. The articles are the result of the February 2006 symposium held in Würzburg and include psychological, neurobiological, historical, and philosophical perspectives. Intending to propose an answer to a question that has been discussed (and revised) over the course of years and many disciplines, the contributors investigate the nature of memory in terms of the biological foundation of autobiographical memory, its subject, narrative structure, and social dimension, as well as the role of forgetting.